Contemporary advertising and integrated marketing communications - Weigold, Michael F; Arens, William F (McGraw Hill LLC, 2024)
"The 17th edition of "Contemporary Advertising and Integrated Marketing Communications' represents the ethics to a broader focus on ethics, diversity, and inclusion. Advertising has made strides in diversifying both its ranks and its messages, in part because America's marketplaces and work spaces are more diverse than ever"--